PENGARUH RETURN ON ASSET DAN INVENTORY TURNOVER TERHADAP HARGA SAHAM - Rachmad Darmawan; Desti Sri Astuti (Universitas La Tansa Mashiro, 2016)
The purpose of this study is to know whether there are significant return on assets and inventory turnover to the stock price either partially or silmultan the company LQ 45. These authors examine the relationship between the stock price as the dependent variable return on assets and inventory turnover as independent variables.The method used in this research is quantitative method with multiple linear analysis, samples were taken with purposiv sampling method, the sample used a total of 39companies and using secondary data from bei namely LQ 45 2015. The test statistic used is the classical assumption test, analysis multiple linear regression analysis andsimultaneous partial correlation, coefficient of determination, hypothesis testing andusing the aid application program SPSS 20.Based on the the t test partially significance value greater than 0.05 is a small 0,003. (2) Inventory Turnover (ITO) significant effect on stock prices, This isindicated with a significance value greater than 0.05 is equal to -0,623. simultaneous F test showed that the Return On Asset and Inventory Turnover significant effect on the stock price with a significance value less than 0.05 is equal to 0.201. And based on the results of data analysis showed that